Evaluating the financial performance by considering the effect of external factors on organization cash flow - Hussein Jalil Mohsin; Sahbaa Abdulqader Ahmed; Dalia Štreimikienė (Contemporary Economics, 2020)
Financial performance is the measure of an organization's productivity and effectiveness. It is used as an indicator of an organization's ability to use available resources in generating returns and profits for its stakeholders. Determinants of financial performance include employee productivity, leadership in the organization and resource use. An organization's financial performance defines its continuity. Stability in an organization is dependent on its financial accounting and management. In the world today, an organization's corporate success is influenced by factors that are often out of its control. The external environment of an organization entails a variety of factors whose existence influences its performance and behaviors. The action of these factors directly or indirectly affects organizations. Organizations have to conform to these external factors for their survival. Organizations are environment-dependent and environment serving. An organization is impacted by the environment in which they operate and its success is solely dependent on its ability to adapt to its environment. Changes in external environment factors have a significant impact on the organization's survival and success. The purpose of this research was to assess the effect of external factors on an organization's cash flow. The aim of the study was to obtain data on these external factors and analyze them with the view of finding out their relationship with financial performance of organizations. Linear regression analysis was to find the correlation between the external factors and organization's financial performance.
Keywords: G00; M00; M41; 330; financial performance; accounting; finance; economics